Generation and evaluation of product concepts by integrating extended axiomatic design, quality function deployment and design structure matrix. (October 2022) - Fazeli, Hamid Reza; Peng, Qingjin
Abstract: Existing product concept generation and evaluation methods are mainly based on designers' experience to determine design schemes in the process of product development, which is time-consuming and ineffective. This paper proposes an approach to generate and evaluate design concepts by integrating the extended axiomatic design, quality function deployment and design structure matrix. Different design domains are mapped for matrix operations to generate feasible concepts based on design criteria. A domain mapping matrix is built to determine technical measures, functional requirements and design parameters based on customer requirements. The proposed approach provides a structured method to quantify, validate and qualify design concepts. A case study of the design of a hand rehabilitation device demonstrates the effectiveness of the proposed method.